A new cytotoxic indole alkaloid from the fungus Penicillium polonicum TY12. Issue 9 (3rd May 2022) - Cai, Xue-Yun; Wang, Jia-Peng; Shu, Yan; Hu, Jun-Tao; Sun, Cheng-Tong; Cai, Le; Ding, Zhong-Tao
Abstract: A new dimeric monoterpene indole alkaloid polonidine A (1 ), along with five known compounds, cyclopenol (2 ), verrucosidin (3 ), fructigenine A (4 ), 3-O-methylviridicatin (5 ) and aurantiomides C (6 ), were isolated from Penicillium polonicum TY12. Their structures were established on the basis of extensive spectroscopic analyses. Compound 1 exhibited moderate cytotoxic activities and moderate antibacterial activity against Bacillus subtilis with MIC of 4.0 μg/mL. Graphical Abstract: